An insidious and deadly complication of mechanical chest compressions in a patient on anticoagulation and the subtle echocardiographic findings that enabled timely diagnosis. Issue 5 (6th March 2018) - Koo, Grace; Goyal, Neha; DeCara, Jeanne M.; Lang, Roberto M.; Addetia, Karima
Abstract : Good‐quality chest compressions improve outcomes in cardiac arrest. While manual chest compressions are suboptimal in this regard, the LUCAS device has been shown to improve the effectiveness of chest compressions during cardiopulmonary resuscitation (CPR). The complication rate associated with mechanical CPR, however, has not been adequately studied. Limited evidence suggests no difference in internal injury between manual and mechanical CPR. We report the case of a patient on anticoagulation who developed a mediastinal hematoma post mechanical CPR and on whom subtle findings on initial echocardiography could have alerted the clinician to this complication early during the clinical course. This case further suggests that there may be special populations of patients in whom we may need to be more vigilant in the use of mechanical CPR.